2014
DOI: 10.1002/jmv.23945
|View full text |Cite
|
Sign up to set email alerts
|

High‐risk human papillomavirus infection in different histological subtypes of renal cell carcinoma

Abstract: Limited data exist regarding whether a high-risk human papillomavirus (HR-HPV) infection increases the risk of developing renal cell carcinoma. The aim of this study was to investigate whether HPV infection has a role in the pathogenesis or development of a certain histological subtype of renal cell carcinoma. Formalin-fixed paraffin-embedded (FFPE) specimens of 122 patients with histopathologically proven renal cell carcinoma and their respective peritumoral tissues were examined. The presence of HPV-DNA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Clear cell renal cell carcinoma is the most common histological subtype of renal cell carcinoma, accounting for ~80% of cases of renal tumors (2). Early diagnosis and medical intervention are vital in decreasing mortality rates and promoting quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Clear cell renal cell carcinoma is the most common histological subtype of renal cell carcinoma, accounting for ~80% of cases of renal tumors (2). Early diagnosis and medical intervention are vital in decreasing mortality rates and promoting quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Other genetic elements, e.g., oncogenes transmitted by cancer-associated viruses, may contribute in DDR and/or cell cycling (11,12). For instance, clinical studies of RCC recently identified presence of DNA from oncogenic human papillomavirus (HPV) 16 or 18 serotypes in 14%–30% of cases (13,14). This should be of interest because HPV oncoproteins may alter DDR and cell cycling (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Microplate hybridization assays were further confirmed by type-specific nested PCR using specific primers to detect HPV16 and HPV18 DNA as described before [20][21][22][23].…”
Section: Type-specific Pcrmentioning
confidence: 99%